Biocompatible Autonomic Self‐healing PVA‐TA Hydrogel with High Mechanical Strength. Issue 13 (7th July 2021) - Huang, Jinxin; Wu, Chengwei; Yu, Xiaogang; Li, Heng; Ding, Shuaiwen; Zhang, Wei
Abstract : Front Cover : In article number 2100061 by Wei Zhang and co‐workers, a high‐strength PVA‐TA hydrogel shows efficient self‐healing performance. The strength is demonstrated through stretching the hydrogel cube. The intermediate fracture network of the hydrogel is gradually healed by the reconstruction of the H bond between the TA and PVA polymer chains.